LOCUS OF CONTROL: A CONCEPT ANALYSIS (The Research of Medical Science Review, 2024)
Purpose: This concept analysis has been done to strengthen the epistemological foundation and to clarify the ontology of the concept “Locus of Control, LOC” by using the Walker and Avant Concept Analysis approach (Walker L. O. & Avant K. C., 2005). Hence, there is no concept analysis has been done on locus of control and locus of control which is an important aspect of personality. Method: This concept analysis was done by using the dictionaries to get the etymologic and semantic meaning of this concept and diverse online literatures ‘PubMed’, CINAHL, Google Scholar & Science Direct were used to analyze this concept and to understand this concept in relation to human nature and specifically nursing. Results: It revealed that emotional stability may be a predisposing factor for internal locus of control. Thus, the study results indicated that people with higher emotional stability and a stronger internal locus of control are more likely to engage in positive behavior. Conclusion: Therefore, to promote positive behavior, people’s self-control awareness must be strengthened through education to enable them to remain calm and peaceful.